Distal oesophageal spasm secondary to eosinophilic oesophagitis in a child: response to diet therapy. Issue 1 (26th June 2019) - Ahsan, Syed Daniyal; Kammermeier, Jochen; Vora, Rakesh; Mutalib, Mohamed
Abstract : We report a case of a school-age child with symptomatic distal oesophageal spasm (DES), clinical dysphagia and typical feature in high-resolution oesophageal manometry secondary to eosinophilic oesophagitis (EoE). His symptoms resolved with normalisation of oesophageal manometry after standard treatment of EoE. DES is mainly an adult disorder and rarely affect children; to the best of our knowledge, this is the first reported case in a child that document full recovery after treating the underlying EoE.